Membangun Kemandirian Ekonomi Siswa SMK melalui Unit Produksi Slipper Hotel Berorientasi Pasar - Rahmawati, Keny (Dharma: Jurnal Pengabdian Masyarakat, 2024)
This community service program focuses on enhancing the operational capacity of the Slipper Hotel Production Unit at SMK PI Ambarrukmo 1 Sleman. The program addresses challenges such as limited equipment, low product diversification, and insufficient digital marketing skills among students and teachers. Through the integration of Teaching Factory (TeFa) and Project-Based Learning, the program provided training in production techniques, branding, and digital marketing. The results include the production of hotel-standard slippers using EVA foam, improved digital marketing skills, and a well-structured organizational system. Despite these achievements, challenges such as limited production tools and lack of product variety persist. Future plans include diversifying eco-friendly products and expanding partnerships with industry stakeholders. This initiative serves as a replicable model for vocational education entrepreneurship to reduce unemployment and support local economies.